DETERMINAN PRESTASI AKADEMIK MAHASISWA KELAS PENGANTAR BISNIS - Anggita Langgeng Wijaya; Nik - Amah (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2012)
ABSTRACT This research tests the determinant academic performance for a sample of fundamental business class. The determinant consist degree of class participation, gender, studying time and part time work as predictor of academic performance. Population of this research is all of new student at first semester from accounting education department at IKIP PGRI Madiun. In this study, sample consist 109 students from three fundamental business class. Hypothesis test of this research uses multiple regression analysis. Classical assumption test and test of normality also use in this research. The results show that: class participation positively affects on student academic performance; gender negatively affects on student academic performance; studying time had no affects on student academic performance; part time work had no affects on student academic performance.   Keywords: class participation, gender, studying time, part time work, student performance.